A world of maximalist medicine: physician perspectives on palliative care and end-of-life for patients with pulmonary arterial hypertension - Brown, Crystal E., MD MA; Steiner, Jill M., MD MS; Leary, Peter J., MD PhD; Curtis, J. Randall, MD MPH; Engelberg, Ruth A., PhD (Journal of pain and symptom management, 2023)
AbstractContextPhysicians who specialize in pulmonary arterial hypertension (PAH) care for patients facing a serious, life-limiting illness. Palliative care is underutilized in patients with PAH, and little is known about how best to provide palliative care to this patient population. ObjectivesUsing a qualitative approach, assess physicians’ perspectives on barriers and facilitators to the use of palliative care in PAH. MethodsParticipants were board-certified pulmonologists and cardiologists recruited from the Pulmonary Hypertension Association's list of physician specialists and academic center websites. We performed one-on-one semi-structured interviews that were recorded, transcribed, and analyzed using thematic analysis. ResultsTwelve physicians participated in the study, with a median age of 48.5 years and 20.5 years of clinical experience caring for patients with PAH. We identified the following themes and associated barriers and facilitators to effective implementation of palliative care for patients with PAH: a tailored approach to the individual patient; a PAH-specialist-led culture of care; effective collaboration with palliative care clinicians; and limitations imposed by health systems. ConclusionPAH physicians are open to palliative care for their patients and are willing to partner with palliative care clinicians to implement this effectively and in the right setting. Areas for targeted improvement in enhancing palliative care for patients with PAH exist, especially enhancing collaboration between PAH physicians and palliative care specialists and navigating barriers in health systems.